Theoretical Justification of the Dynamic Parameters in Plant Stems Sliding Cutting - Tarverdyan, A. P.; Altunyan, A. V. (ՀԱԱՀ հիմնադրամ)
The first article of the series considers the opportunities of finding theoretical solutions to the issue of plants stem cutting via sliding method with account for the rheological properties of the substance. Throughout the problem solution, cutting process was viewed as a transitional step for forced crack propagation in the body. Analytical expressions have been derived, which enable to analyze the stress state of the material in the cutting zone, to identify the principal stresses causing abrasions in case of sliding cutting. Intensity coefficient, sliding coefficient and their value domains have been identified, whereby the sliding cutting is implemented with minimum energy consumption.
Keywords: Agricultural Engineering